DIFFERENT APPROACHES TO THE DEFINITION OF THE CONCEPT "INFORMATION CULTURE" IN SCIENTIFIC LITERATURE (Pedagogy of Higher and Secondary Education, 2004)
The different methodological approaches for définition of the essence of the notion information culture are analyzed. The author gives his own définition of the sociocultural phenomenon.